2011
DOI: 10.1152/ajpcell.00046.2011
|View full text |Cite
|
Sign up to set email alerts
|

Air bubble contact with endothelial cells in vitro induces calcium influx and IP3-dependent release of calcium stores

Abstract: Gas embolism is a serious complication of decompression events and clinical procedures, but the mechanism of resulting injury remains unclear. Previous work has demonstrated that contact between air microbubbles and endothelial cells causes a rapid intracellular calcium transient and can lead to cell death. Here we examined the mechanism responsible for the calcium rise. Single air microbubbles (50-150 μm), trapped at the tip of a micropipette, were micromanipulated into contact with individual human umbilical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 45 publications
2
49
0
Order By: Relevance
“…Concentrations of these inhibitors were chosen based on their abilities to significantly reduce, but not completely, histamine-induced calcium responses. Higher concentrations or longer exposure induced cytotoxicity during preincubation time as also observed by Sobolewski and colleagues (35). The inactive U-73122 analog, U-73343, was purchased from Enzo Life Sciences (Farmingdale, NY) and used at same final concentration.…”
Section: Methodsmentioning
confidence: 61%
See 1 more Smart Citation
“…Concentrations of these inhibitors were chosen based on their abilities to significantly reduce, but not completely, histamine-induced calcium responses. Higher concentrations or longer exposure induced cytotoxicity during preincubation time as also observed by Sobolewski and colleagues (35). The inactive U-73122 analog, U-73343, was purchased from Enzo Life Sciences (Farmingdale, NY) and used at same final concentration.…”
Section: Methodsmentioning
confidence: 61%
“…The existence of an equivalent delay in calcium response can also be observed with a reduction of shear magnitude, and an activation threshold of the applied shear stress was suggested (2). In a model of mechanical forces applied by micropipettes on isolated ECs, the calcium response also reaches a maximum within 10 -20 s and was further delayed by used of membrane calcium channel blockers (35). Overall, these data and ours strongly suggest that mechanically induced calcium responses require a threshold for activation and that any reduction in mechanical cue or treatment aiming at reducing accumulation of a second messenger only delays the threshold required for the calcium response.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to an increase in endothelial layer permeability, several other bioeffects have also been reported by others, such as a rise in intracellular calcium ions [9], [10], [ca 2+ ] i , and reactive oxygen species (ros) formation [11]. Interestingly, all of these responses have also been reported in endothelial cells following mechanotransduction [6], [12]- [14]. because mechanotransduction can lead to an increase in [ca 2+ ] i and/or ros, and subsequently to an increase in endothelial layer permeability, we determined whether this was also involved in microbubble-mediated increases in endothelial layer permeability.…”
mentioning
confidence: 78%
“…Previously, it has been shown that cells respond in conventional and in inverted interface experiments with intracellular Ca 2ϩ signals (55,56,63). Here we extended those studies using agonists and inhibitors for various channels and pathways (Fig.…”
Section: Conventional Interface Experiments Seementioning
confidence: 99%